2017
DOI: 10.1377/hlthaff.2017.0610
|View full text |Cite
|
Sign up to set email alerts
|

High-Deductible Health Plans Reduce Health Care Cost And Utilization, Including Use Of Needed Preventive Services

Abstract: Enrollment in high-deductible health plans (HDHPs) has greatly increased in recent years. Policy makers and other stakeholders need the best available evidence about how these plans may affect health care cost and utilization, but the literature has not been comprehensively synthesized. We performed a systematic review of methodologically rigorous studies that examined the impact of HDHPs on health care utilization and costs. The plans were associated with a significant reduction in preventive care in seven of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
89
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(99 citation statements)
references
References 38 publications
10
89
0
Order By: Relevance
“…As Agarwal et al. noted in their 2017 systematic review of the relationship between HDHP and healthcare use, HDHP were associated with lower cost due to reduction in healthcare consumption, including preventive care …”
Section: Impact Of the Ppacamentioning
confidence: 99%
See 1 more Smart Citation
“…As Agarwal et al. noted in their 2017 systematic review of the relationship between HDHP and healthcare use, HDHP were associated with lower cost due to reduction in healthcare consumption, including preventive care …”
Section: Impact Of the Ppacamentioning
confidence: 99%
“…For individuals not covered by employer plans or public programs, such as Medicare or Medicaid, insurance products were offered through health exchanges. 37 Wharam et al reported earlier this year that HDHP were associated with virtually all aspects of care among newly diagnosed women with early-stage breast cancer, including imaging, biopsy, diagnosis, and chemotherapy initiation. 38 In contrast, Lu et al did not find delays in the utilization of adjuvant hormone therapy among women switching into HDHP.…”
Section: Emergence Of High Deductible Plans To Individual (Insurance)mentioning
confidence: 99%
“…The prevalence of high‐deductible health plans among adults enrolled in employer‐sponsored insurance is increasing rapidly over time . There is mounting evidence that enrollment in high‐deductible health plans is associated with reduced health care utilization . Theoretically, there may be at least two pathways through which high‐deductible health plan enrollment and low health care utilization are connected.…”
Section: Introductionmentioning
confidence: 99%
“…8 For these reasons, controlling type 2 diabetes is "one of the most important public health challenges of the twenty-first century." 11(p1) A recent systematic review by Agarwal and colleagues 12 assessed the association between enrollment in HDHPs and clinical and economic outcomes. Consistent with the findings of the RAND Health Insurance Experiment, 13 Agarwal et al 12 concluded that HDHPs can achieve savings by reducing the use of appropriate and inappropriate care alike.…”
Section: Introductionmentioning
confidence: 99%